2006
DOI: 10.1021/ja057157h
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Heterostructured GaP−GaAs Nanowires

Abstract: We have studied the vapor-liquid-solid (VLS) growth dynamics of GaP and GaAs in heterostructured GaP-GaAs nanowires. The wires containing multiple GaP-GaAs junctions were grown by the use of metal-organic vapor phase-epitaxy (MOVPE) on SiO(2), and the lengths of the individual sections were obtained from transmission electron microscopy. The growth kinetics has been studied as a function of temperature and the partial pressures of the precursors. We found that the growth of the GaAs sections is limited by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
198
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(212 citation statements)
references
References 33 publications
12
198
2
Order By: Relevance
“…The growth of GaP nanowires has been well characterized for various conditions and substrates. 23,24 Nanowires were grown using a metalloorganic vapor epitaxy following the method of ref 20. A combination of vapor-liquid-solid (VLS) and lateral growth processes was used to precisely tune the diameter of the wires while keeping the nanowire density fixed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of GaP nanowires has been well characterized for various conditions and substrates. 23,24 Nanowires were grown using a metalloorganic vapor epitaxy following the method of ref 20. A combination of vapor-liquid-solid (VLS) and lateral growth processes was used to precisely tune the diameter of the wires while keeping the nanowire density fixed.…”
mentioning
confidence: 99%
“…In this way the wire diameter can be changed without creating extremely long nanowires. 24 After growth, the samples were cooled down in a PH 3 containing atmosphere.…”
mentioning
confidence: 99%
“…Among several possible device configurations, the axial heterojunction and pn-junction structures are obviously advantageous, because they can be directly formed during VLS nanowire growth by a switching of the source material; hence they do not require additional junction fabrication processes. However, instead of possessing the ideal u Fax: +1-919-660-8963, E-mail: ttan@duke.edu abruptness on an atomic scale, NW heterojunctions grown via the VLS method always have graded composition transition regions with a relatively large junction width [4,5,7], i.e., a sizable fraction of the nanowire diameter. We suggest that this phenomenon is a characteristic feature of the VLS growth method.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, extensive studies have been performed on the preparation, property, and growth kinetics of nanowires and nanowire structures with either hetero-or pn-junctions [1][2][3][4][5][6][7][8][9]. Nanowire heterojunction structures of various semiconductors have been fabricated, e.g., Si-Ge [3][4][5], GaAs-InAs [6] and GaP-GaAs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…62 Moreover, as we have stated in section 'Recent progress in DFT modeling on the atomistic structure of NHSs', on the surface of the base nanomaterial, the reactivities of different sites (steps or facets) are different and they show distinct affinities towards the deposition of the second components. For example, Bakkers et al 63 demonstrated that in the growth process of a GaP-GaAs NHS, the rate of GaP deposition onto the tips was two orders of magnitude higher than that of the growth on the sidewall. In a practical synthetic system, if the reaction kinetics are slow or the feed amount of the precursor is limited, the second component would tend to deposit onto the most active site, whereas if large amounts of raw materials are supplied, the thermodynamic differences between the different sites would be concealed.…”
Section: Rational Synthesis and Structure-property Relationships Of Nmentioning
confidence: 99%